2014
DOI: 10.5430/cns.v2n2p133
|View full text |Cite
|
Sign up to set email alerts
|

Using tethered-personal health records for pre-liminary end-of-life discussions with medical providers: Preferences of African American vs. Caucasian primary care patients

Abstract: Background: End-of-life discussions rarely begin early in a patient's disease course due to the time intensive nature of these conversations. Neglect of such conversations often results in poor understanding about a patient's care preferences. Electronic health record (EHR)-tethered Personal Health Records (PHRs) are being used more widely in chronic disease management and may provide a time efficient vehicle to embark on early end-of-life conversations, also known as Advance Care Planning (ACP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…It is important to note that many of the unaddressed problems highlighted in previous literature reviews are likely to still be problems despite being out of the scope of this review. For instance, many prior studies have cited usability issues with portals, 124,[152][153][154][155][156][157][158][159][160][161][162][163] but it was not a major finding in our review. This does not mean that problems such as inconsistency across platforms are not still issues, especially considering that a recent survey of U.S. adults found that 44% of those with a portal account were managing two or more accounts.…”
Section: Limitationsmentioning
confidence: 85%
“…It is important to note that many of the unaddressed problems highlighted in previous literature reviews are likely to still be problems despite being out of the scope of this review. For instance, many prior studies have cited usability issues with portals, 124,[152][153][154][155][156][157][158][159][160][161][162][163] but it was not a major finding in our review. This does not mean that problems such as inconsistency across platforms are not still issues, especially considering that a recent survey of U.S. adults found that 44% of those with a portal account were managing two or more accounts.…”
Section: Limitationsmentioning
confidence: 85%
“…Expanded use of patient portals linked to electronic health records (EHRs) has increased individuals' involvement in disease self‐management and engagement with providers. A patient portal can be a vehicle for efficient, quality ACP communication, but age‐based willingness of individuals to use patient portals for ACP communication must be assessed …”
mentioning
confidence: 99%